Alternative treatment of olive mill wastewater by combined sulfate radical-based advanced electrocoagulation processes - Guvenc, Senem Yazici; Tunc, Sinan (WILEY, 2023)
The aim of this study is to investigate the performance of advanced electrocoagulation (EC) process for the treatment of olive mill wastewater. In EC process, iron plates were used as electrodes, and peroxydisulfate (PS) and peroxymonosulfate (PMS) were added as oxidants. The effects of the initial pH value, current density, oxidant dose, and electrolysis time were optimized for pollutant removal from olive mill wastewater by EC-PS and EC-PMS processes. Control experiments showed that addition of oxidants to the conventional EC process increased the pollutant removal efficiency. Classical optimization method was used to determine optimum conditions, which were initial pH 4, current density 40 mA/cm2, oxidant dose 5 g/L, and electrolysis time 30 min for both processes. Under these conditions, EC-PS and EC-PMS processes achieved 50.5% and 48.9% chemical oxygen demand (COD), 93.8% and 89.3% total phenol, 87.7% and 83% UV254, and 74.5% and 64.1% total suspended solid removal efficiencies. Quenching experiments were performed to determine the dominant radical species participating in the processes. It was observed that hydroxyl and sulfate radicals were involved in both processes but hydroxyl radicals were more active. Specific energy consumption was calculated as 5.90 kWh/kg COD for EC process, 4.95 kWh/kg COD for EC-PS process, and 5.20 kWh/kg COD for EC-PMS process. The organic removal/sludge ratio of EC-PS process was found to be higher with 17.5 g/L value. Although the application of EC-PS and EC-PMS processes alone is insufficient to meet the discharge limits, they have been found to be effective in olive mill wastewater treatment.Practitioner PointsPeroxydisulfate (PS) and peroxymonosulfate (PMS)-based advanced electrocoagulation (EC) was used in olive mill wastewater treatment.50.5% chemical oxygen demand (COD), 93.8% TP, 87.7% UV254, and 74.5% TSS removals were achieved by EC-PS.48.9% COD, 89.3% TP, 83% UV254, and 64.1% TSS removals were obtained by EC-PMS.Hydroxyl and sulfate radicals were involved in both processes. Under optimum conditions, 50.5% and 48.9% chemical oxygen demand removal and 93.8% and 89.3% total phenol removal using advanced electrocoagulation (EC)-peroxydisulfate (PS) and EC-peroxymonosulfate (PMS) processes, respectively. EC-PS and EC-PMS processes were both effective in olive mill wastewater treatment; however, they were not sufficient enough to meet the discharge limits alone.image
Keywords: advanced electrocoagulation; effective radical species; energy cost; olive mill wastewater; peroxydisulfate; peroxymonosulfate; sludge analysis; LANDFILL LEACHATE TREATMENT; ACTIVATED PERSULFATE; FENTON PROCESS; ELECTROCHEMICAL OXIDATION; ORGANIC CONTAMINANTS; AQUEOUS-SOLUTION; DEGRADATION; ACID; OPTIMIZATION; REMOVAL; Engineering; Environmental Sciences & Ecology; Marine & Freshwater Biology; Water Resources